MATHEMATICAL MODELLING OF THE INFLUENCE OF WEATHER FACTORS ON THE FORMATION OF THE FUND OF POLYPHENOLIC SUBSTANCES IN CHERRY FRUITS - Пендрак, Ярослав; Іванова, Ірина; Сердюк, Марина; Тимощук, Тетяна; КРИВОНОС, Ірина (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Cherry is a popular and widespread fruit crop in many European countries. The scientific efforts of researchers today are aimed at determing the quality indicators of the spectrum of modern cherry varieties and their selection for further table and technological use by the most important biochemical components. In this regard, this work is devoted to the study of accumulation of poliphenolic substances in cherry varieties. The aim of the research was to buid and analyse a mathematical model that would allow determining the degree of weather factors influence on the dynamics of poliphenolic substances accumulation in cherry fruits of model varieties. The model varieties were the fruits cherry varieties registered in the State Register of plant varieties suitable for distribution in Ukraine (names of varieties). The study of accumulation of poliphenolic substances in the fruits of 10 model cherry varieties showed that the variety 'Ihrushka' was characterised by the lowest variability in the content of the quality indicator with a value of the coefficient of variation of 9,9%. The optimum average value of phenolic substances (224,615mg per 100g) was found in the fruits of cherry variety 'Siianets Turuvtsevoi' (Vp - 12,8%). The conducted two factor analysis variance made it possible to determine the dominant influence of varietal characteristics (factor B) on the formation of the fund of polyphenolic substances in cherry fruits. The influence share of factor B was 41,3%. The correlation analysis showed the presence of a correlation linear relationship between the seven weather factors and the content of polyphenolic substances in cherry fruits. The study of the constructed regression model for determining and ranking weather factors according to the degree of their influence of the studied fruit quality indicator showed that the average monthly amount of precipitation in June was decisive for the accumulation of the fund of polyphenolic substances.
Keywords: phenolic compounds, pomological variety,; fruit ripening time,; variability,; factor; weather conditions; stone fruit,; cherry; ridge-regression